PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH DAN DANA ALOKASI UMUM TERHADAP KEMANDIRIAN DAERAH (Studi Kasus Pada Kabupaten/Kota Di Propinsi Bali Periode 2011-2015) - Wahyuningsih, Panca (JAB (Jurnal Akuntansi & Bisnis), 2015)
Financial independence is the goal of every area to improve the life of an area. The more independent the region is improving people's welfare.The purpose of this study was to determine whether the Influence of Local Taxes, Levies, and General Allocation Fund on The Level Regional Financial Independence at district or city government of Bali Province. The method to use a causal research design with a sample of eight county and one city in the province of Bali. This research was conducted for the periods of 2011 to 2015. Data used is secondary data. The data analyzed in this study compiled from Budget Realization Report. The data have been collected and analyzed by the method of data analysis first conducted classical assumption test before performing multiple linear regression testing f tes, t test, and test the coefficient of determination. The analysis showed that partially local taxes and lavies positive effect on the level of local financial independence. While the general allocation fund and no significant negative effect on the level of local financial independence. Simultaneously, local taxes, levies, and general allocation fund a positive effect on the level of local financial independence. Keywords: Level Regional Financial Independence, Regional Tax, Retribution, and General Allocation Fund.